(untitled) (Global Journal of Human-Social Science, 2020)
The economic growth model of advancement had challenged by the UNDP in its first Human Development Report 1990, which emphasized that individuals, not things, are the abundance of countries, and it is they who ought to be the focal point of an improvement coordinated to ’extending their decisions.’ Three fundamental abilities are identified as requirements to a real existence that is rich with potential and the fulfillment of one’s goals: the ability to lead long lives, access to information and the boundless vistas that it opens to the questing mind, and the capacity to guarantee for oneself a sensibly decent way of life. Without these assets, individuals’ decisions are limited, and life’s chances are far off. Human development is the procedure of building these abilities to empower individuals to lead fulfilling and beneficial life. In this regard, present paper aims to know improvements in human development, comparing to other states; concentrates on the status of various dimensions of human development index, and finally, acquiring the status of human development in the Hyderabad Karnataka region at Grama Panchayat level.